2023
DOI: 10.1111/liv.15549
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical liver traits are associated with structural and hemodynamic brain imaging markers

Abstract: Background & Aims: Impaired liver function affects brain health and therefore understanding potential mechanisms for subclinical liver disease is essential. We assessed the liver-brain associations using liver measures with brain imaging markers, and cognitive measures in the general population. Methods: Within the population-based Rotterdam Study, liver serum and imaging measures (ultrasound and transient elastography), metabolic dysfunction-associated fatty liver disease (MAFLD), non-alcoholic fatty liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Others have also interestingly reported an association of NAFLD with altered executive and frontal lobe function, depressive mood, anxiety, and apathy ( Moretti et al, 2019 ). Further linking liver function and brain health, in a large population-based study of over 3,400 patients without dementia or prior stroke, NAFLD was found to be associated with alterations in white matter microstructural integrity, lower cerebral blood flow, and lower brain perfusion as evaluated using MRI ( Yilmaz et al, 2023 ). Animal studies have found similar changes to cerebral brain volume and suggest altered metabolism may be contributing to this.…”
Section: Liver-brain Axis In Clinical Diseasementioning
confidence: 99%
“…Others have also interestingly reported an association of NAFLD with altered executive and frontal lobe function, depressive mood, anxiety, and apathy ( Moretti et al, 2019 ). Further linking liver function and brain health, in a large population-based study of over 3,400 patients without dementia or prior stroke, NAFLD was found to be associated with alterations in white matter microstructural integrity, lower cerebral blood flow, and lower brain perfusion as evaluated using MRI ( Yilmaz et al, 2023 ). Animal studies have found similar changes to cerebral brain volume and suggest altered metabolism may be contributing to this.…”
Section: Liver-brain Axis In Clinical Diseasementioning
confidence: 99%
“…In the physiologically healthy populace, serum GGT is primarily liver-derived, and its levels tend to escalate in response to hepatic damage [15,16]. GGT exhibits a close a nity with systemic oxidative stress and in ammation, frequently displaying overexpression in malignant neoplasms, thereby bolstering tumor cell survival and proliferation [17]. Previous academic explorations have attested that ampli ed pre-treatment GGT levels augur adverse prognosis in patients a icted with various malignant tumors, including esophageal cancer, renal cancer, prostate cancer, and intrahepatic cholangiocarcinoma [14,18,19].…”
Section: Introductionmentioning
confidence: 99%